The Channel-width Dependence of the Low-temperature Hole Mobility in Ge-rich Narrow Square Quantum Well Studied by the Band-bending Method - Hai, Tran Thi; Hong, Nguyen Trung; Tung, Nguyen Huyen; Quang, Doan Nhat (Communications in Physics, 2012)
We employ the theory of band-bending effects to explain the channel-width dependence of the mobility of a two-dimentional hole gas (2DHG) in narrow square Si/Si\(_1-x\)Ge\(_x\)/Si quantum well at high Ge content. The numerical calculation of scattering mechanisms is shown in comparison with the ones from the previous computations. Our method enables a better quantitative description of recently measured data about the dependence of the 8 K mobility of holes in a Si/Si\(_0.2\)Ge\(_0.8\)/Si quantum well on the channel width varying from 25 - 70Å